Anti-static foaming silica gel buffer piece for new energy battery and preparation method of anti-static foaming silica gel buffer piece
By optimizing the composition and structural design of the antistatic compound, using acetylene black and single-walled carbon nanotubes to form a stable framework, and combining organosilicon oligomers and amine activators, the performance degradation problem of antistatic foamed cushioning components under harsh environments was solved, achieving efficient cushioning and durable antistatic performance.
Patent Information
- Application Number
- CN202511229694.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-12-02
AI Technical Summary
Existing antistatic foam cushioning components struggle to maintain optimal cushioning and antistatic performance during long-term use, especially under harsh environmental conditions. Particularly in high-temperature and high-humidity environments, the bonding force between the silicone matrix and the antistatic filler decreases, disrupting the continuity of the conductive network and leading to a decline in cushioning and antistatic performance.
The antistatic compound is composed of methyl vinyl silicone rubber raw rubber, silica, antistatic filler, and hydrogen-containing silicone oil. It forms a stable supporting antistatic framework structure through acetylene black and single-walled carbon nanotubes. It is combined with organosilicon oligomers and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine to form a synergistic activation system, which enhances the interfacial bonding force and ensures that the cushioning component maintains structural stability and antistatic performance during long-term use.
The resulting antistatic foamed silicone buffer exhibits a compression resistance retention rate of over 95% during long-term use, with an electrostatic value ranging from 10⁶ to 10⁸. It maintains excellent buffering and antistatic performance under high and low temperature cycling and frequent compression, significantly improving the safety of battery use.
Smart Images

Figure BDA0005573496800000061 
Figure BDA0005573496800000091
Abstract
Description
Technical Field
[0001] This application relates to the field of new energy battery buffer components, and more specifically, it relates to an antistatic foamed silicone buffer component for use in new energy batteries and a method for preparing the same. Background Technology
[0002] With the rapid development of new energy technologies, the application scope of power batteries and energy storage batteries is constantly expanding. During battery assembly and use, buffer components play a crucial role in mitigating volume expansion stress during charging and discharging, as well as protecting battery electronic components. In particular, anti-static foamed buffer components can effectively conduct away static charges generated during assembly and handling, thereby further ensuring the safe and stable operation of the battery. The booming development of the new energy battery industry has placed higher demands on the performance of buffer components, whose performance directly affects the battery's lifespan and safety. In practical applications, whether it's the power battery of electric vehicles or the energy storage battery of large-scale energy storage power stations, reliable buffer components are essential to ensure their normal operation.
[0003] Prior to this technical solution, the mainstream antistatic foam cushioning components on the market were mainly EPDM antistatic foam and EVA foam, while the use of silicone antistatic foam was relatively limited. Although some research has attempted to prepare cushioning materials by foaming silicone rubber, existing technologies still have many shortcomings.
[0004] Silicone rubber foam materials possess good high-temperature resistance and aging resistance, making them suitable for applications requiring high environmental adaptability. However, existing silicone rubber foam cushioning components struggle to maintain optimal cushioning and antistatic properties during long-term use, especially in high-temperature and high-humidity environments. For instance, high-temperature and high-humidity environments may reduce the bonding force between the silicone matrix and the antistatic filler, disrupting the continuity of the conductive network. High humidity allows moisture to penetrate the microporous structure of the foamed silicone, accelerating aging and affecting its antistatic and cushioning performance. Furthermore, under severe vibration or impact, delamination or cracks may occur within the silicone rubber foam cushioning component, physically severing the conductive network and creating "antistatic blind spots." Additionally, during repeated volume expansion and compression fatigue of the battery cell, if the cushioning component's compression resistance is insufficient, the micropores of the foam structure may irreversibly collapse, simultaneously impacting both cushioning and antistatic performance.
[0005] In summary, existing antistatic foam cushioning components struggle to maintain optimal cushioning and antistatic performance during long-term use, especially under harsh environmental conditions. Therefore, current antistatic foam silicone cushioning components for new energy batteries cannot meet the ever-increasing demands for high performance during long-term use and urgently require further research and improvement. Summary of the Invention
[0006] The purpose of this application is to solve the problem of maintaining good cushioning and antistatic performance of antistatic foamed buffers during long-term use, especially under harsh environmental conditions, and to provide an antistatic foamed silicone buffer for new energy batteries and its preparation method.
[0007] In a first aspect, an antistatic foamed silicone buffer for new energy batteries is provided. This antistatic foamed silicone buffer is prepared by mixing and foaming an antistatic compound, a foaming agent, hydrogen-containing silicone oil, an inhibitor, and a platinum catalyst. The antistatic compound is composed of the following raw materials by weight percentage: 37-50% methyl vinyl silicone rubber raw rubber, 38-45% silica, 8-15% antistatic filler, and 1-3% hydroxyl silicone oil. The antistatic filler is composed of an antistatic agent and a silane-containing activator. The antistatic agent is composed of acetylene black and single-walled carbon nanotubes.
[0008] By adopting the above technical solutions, methyl vinyl silicone rubber raw rubber imparts good flexibility and elasticity to the cushioning component, laying the foundation for its cushioning performance. Silica acts as a reinforcing agent, enhancing the material's mechanical strength and enabling the cushioning component to withstand certain external impacts. The acetylene black and single-walled carbon nanotubes in the antistatic agent intertwine and work synergistically to form a stable supporting antistatic skeleton structure, effectively conducting static electricity, preventing static accumulation, achieving good antistatic performance, and maintaining structural stability during long-term use, ensuring the cushioning component's compression recovery performance and antistatic durability. Hydroxyl silicone oil adjusts the viscosity of the silicone rubber and optimizes the uniformity of silica dispersion. The synergistic effect of these materials ensures that the cushioning component achieves a compression resistance retention rate of over 95% after vibration and impact fatigue testing, and a static electricity value below 10 after high and low temperature cycling testing. 6 -10 8 Within this range, the overall performance of the cushioning component in terms of compression resistance and antistatic durability has been significantly improved.
[0009] Preferably, the amount of acetylene black is 4-7 wt%; the amount of single-walled carbon nanotubes is 2-5 wt%; and the amount of silane activator is 3-5 wt%.
[0010] By adopting the above technical solution and optimizing the dosage of acetylene black, single-walled carbon nanotubes and silane-containing surfactants, acetylene black and single-walled carbon nanotubes can better interweave and work synergistically to form a more stable supporting antistatic skeleton structure. This further improves the antistatic performance and compression resistance of the buffer, ensuring that the buffer maintains high buffering performance and stable antistatic performance under long-term use, repeated compression, impact and cold and hot environment tests.
[0011] Preferably, the particle size of both the acetylene black and the single-walled carbon nanotubes is 0.001-10 micrometers.
[0012] By adopting the above technical solution, the particle size of acetylene black and single-walled carbon nanotubes is controlled within 0.001-10 micrometers. This allows for thorough and uniform mixing with the antistatic compound raw material system under the synergistic effect of a silane-containing activator. During subsequent mixing and foaming processes, they intertwine and work synergistically to form a stable supporting antistatic skeleton structure, effectively conducting static electricity and preventing its accumulation. Furthermore, the structure remains stable even after repeated compression, impact, and exposure to hot and cold environments during long-term use, ensuring the compression resilience and antistatic durability of the cushioning component. After vibration and impact fatigue testing, the compression resistance retention rate of the cushioning component reaches over 95%, and after high and low temperature cycling testing, the static electricity value is 10. 6 -10 8 Within the range.
[0013] Preferably, the siloxane-containing activator is composed of an organosilicon oligomer and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine.
[0014] By adopting the above technical solution, organosilicon oligomers and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine form a synergistic activation system. The amine silane reacts with the hydroxyl groups on the surface of the antistatic filler through the trimethoxysilane group, and at the same time combines with the silicone rubber matrix through the hydroxyethyl and amine groups, realizing the chemical anchoring of the filler and the matrix. The organosilicon oligomer crosslinks with the vinyl groups of silicone rubber and the active groups of amine silane through the active groups, forming an "elastic transition layer" on the surface of the filler, which not only enhances the interfacial bonding force, but also buffers the impact of compressive stress on the conductive network. The synergy of the two makes the antistatic filler uniformly dispersed and forms a composite interface of "rigid connection-flexible buffer" with the matrix, which significantly inhibits the migration of filler and network breakage under repeated compression, and improves the compression resistance and antistatic durability.
[0015] Preferably, the organosilicon oligomer is a methacryloyloxypropyl organosilicon resin and / or a glycidyl etheroxypropyl organosilicon oligomer.
[0016] By employing the above technical solution, methacryloyloxypropyl silicone resin and / or glycidyl etheroxypropyl silicone oligomers form a synergistic activation system with N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine. The silicone oligomers crosslink with the vinyl and amine silane active groups of silicone rubber through active groups (double bonds / epoxy groups), forming an "elastic transition layer" on the filler surface. This layer enhances interfacial bonding and buffers the impact of compressive stress on the conductive network. Synergistically with the amine silane, it ensures uniform dispersion of the antistatic filler, forming a "rigid connection-flexible buffer" composite interface with the matrix. This significantly inhibits filler migration and network breakage under repeated compression, thereby improving the compression resistance and antistatic durability of the buffer component.
[0017] Preferably, the silica is composed of fumed silica and precipitated silica.
[0018] By employing the above technical solution, a balance between performance, cost, and processability can be achieved by mixing fumed silica and precipitated silica. Fumed silica provides high strength and high-temperature resistance, while precipitated silica reduces costs and improves processing fluidity. The combination of the two reduces the agglomeration of fumed silica, optimizes filler dispersion, and avoids processing difficulties caused by excessively high system viscosity. Simultaneously, methyl vinyl silicone rubber raw rubber, as an elastic matrix, forms a matrix-reinforcing network with silica. Silica binds to the silicone rubber molecular chains through hydroxyl groups, enhancing the skeletal strength. Hydroxyl silicone oil optimizes the dispersion uniformity of silica by adjusting the viscosity of silicone rubber. These three components synergistically construct a matrix structure that combines elasticity and rigidity, laying the foundation for the compressive strength after subsequent foaming. Furthermore, the synergistic effect of the "point-to-line" conductive network of the antistatic agent, the dual-component synergistic effect of the siloxane-containing activator, and the overall synergistic effect of the system enable the foamed silicone buffer to exhibit excellent performance durability. In terms of compression resistance, the "matrix-fumed silica" skeleton provides basic support, while the "activator-antistatic agent" interface layer disperses stress. In terms of antistatic properties, the "point-to-line" conductive network remains stable under the anchoring of the activator. Even after high and low temperature cycling tests, the performance is as high as 95%, which can not only provide stable buffer protection but also maintain antistatic performance for a long time, significantly improving the safety of battery use.
[0019] Preferably, the amount of fumed silica is 18-20 wt%, and the amount of precipitated silica is 20-25 wt%.
[0020] By adopting the above technical solution, a balance between performance, cost, and processability can be achieved by combining fumed silica and precipitated silica in this dosage. Fumed silica provides high strength and high-temperature resistance, while precipitated silica reduces costs and improves processing fluidity. The combination of the two also reduces the agglomeration of fumed silica, optimizes filler dispersion, and avoids processing difficulties caused by excessively high system viscosity. Simultaneously, this dosage combination, along with raw materials such as methyl vinyl silicone rubber raw rubber, antistatic fillers, and hydroxyl silicone oil, as well as foaming agents, hydrogen-containing silicone oils, inhibitors, and platinum catalysts, can produce antistatic foamed silicone cushioning components that exhibit excellent compression resistance and durable antistatic properties. This allows them to maintain high cushioning performance under long-term, frequent compression applications and stable antistatic performance under harsh environmental conditions.
[0021] Preferably, the antistatic compound is prepared by the following method: weighing an antistatic agent and a silane-containing activator by weight percentage, mixing them evenly, and activating them to obtain an antistatic filler; weighing methyl vinyl silicone rubber raw rubber, silica, antistatic filler, and hydroxyl silicone oil by weight percentage and kneading them to obtain an antistatic compound.
[0022] By adopting the above technical solution, the antistatic agent and the silane-containing activator are mixed evenly and activated to obtain the antistatic filler, which is then kneaded with methyl vinyl silicone rubber raw rubber, fumed silica and hydroxyl silicone oil to obtain the antistatic compound. This helps to ensure that the raw materials are fully mixed and exert a synergistic effect, laying the foundation for the preparation of antistatic foamed silicone cushioning parts with good compression resistance and antistatic durability.
[0023] Preferably, the foaming agent is composed of sodium bicarbonate and OBSH; the platinum catalyst is a 5000 PPM platinum complex.
[0024] By adopting the above technical solution, the antistatic foamed silicone cushioning component is prepared by mixing and foaming antistatic compound, foaming agent, hydrogen-containing silicone oil, inhibitor, and platinum catalyst. The antistatic compound is composed of methyl vinyl silicone rubber raw rubber, silica, antistatic filler, and hydroxyl silicone oil in a specific ratio. The antistatic filler is composed of antistatic agent and silane-containing activator. The antistatic agent is composed of acetylene black and single-walled carbon nanotubes. Based on this, the foaming agent is composed of sodium bicarbonate and OBSH, and the platinum catalyst is a 5000PPM platinum complex, which enables the materials to work synergistically to ensure that the cushioning component has good flexibility, elasticity, and mechanical strength. The acetylene black and single-walled carbon nanotubes interweave to form a stable antistatic skeleton structure, achieving good antistatic performance and ensuring compression rebound and antistatic durability. After vibration and impact fatigue testing, the compression retention rate is over 95%, and after high and low temperature cycling testing, the static electricity value is below 10. 6 -10 8 Within the specified range, it maintains stable buffering and antistatic properties.
[0025] Preferably, it is prepared by the following method: weigh the antistatic compound and foaming agent by weight percentage, mix them evenly, add hydrogen-containing silicone oil and continue to mix evenly, add inhibitor and mix evenly, and finally add platinum vulcanizing agent and mix evenly. The above mixing process is carried out by mixing in a triangular bag and keeping the mixing temperature below 30°C. The obtained compound is pressed into sheets and then foamed to make antistatic foamed silicone cushioning parts.
[0026] By adopting the above technical solution, each raw material is weighed and mixed according to a specific weight percentage. The mixing is done in a triangular bag and the temperature is kept below 30°C. This ensures that the raw materials are fully and evenly mixed, avoiding adverse effects on the performance of the raw materials due to high temperature. The antistatic foamed silicone buffer, after being pressed and foamed, can fully utilize the advantages brought by the synergistic effect of the antistatic compound, foaming agent, hydrogen-containing silicone oil, inhibitor, platinum catalyst, and other raw materials in the antistatic compound. This improves the compression resistance and antistatic performance durability of the buffer, enabling it to better meet the requirements of new energy batteries for buffering and antistatic performance.
[0027] In summary, this application includes at least one of the following beneficial technical effects: 1. Methyl vinyl silicone rubber raw rubber gives the cushioning component good flexibility and elasticity, while silica reinforcement enhances mechanical strength. The two work together to enable the cushioning component to withstand external impacts without being easily damaged. 2. Under the action of silane-containing activators, acetylene black and single-walled carbon nanotubes intertwine to form a stable supporting antistatic skeleton structure, which can effectively conduct static electricity, avoid static electricity accumulation, and maintain structural stability during long-term use, ensuring the compression rebound performance and antistatic durability of the buffer component. 3. The prepared antistatic foamed silicone buffer component, after vibration and impact fatigue testing, exhibits a compression resistance retention rate of over 95%. After high and low temperature cycling testing, its electrostatic value remains below 10. 6- 10 8 Within a certain range, it can maintain its buffering and antistatic properties under long-term, frequent compression and harsh environments. Attached Figure Description Detailed Implementation
[0028] The present application will be further described in detail below with reference to the embodiments.
[0029] Introduction to some raw materials: Methacryloxypropyl silicone resin brand and model MA902 is a methacryloyloxypropyl silicone resin containing silaneoxy groups. Brands and models of glycidyl etheroxypropyl organosilicon oligomers EP904 is an epoxy-modified silicone resin containing silanoxy groups; Methyl vinyl silicone rubber raw material: number average molecular weight of 100,000-200,000, vinyl content of 0.85-1.05%; Hydroxysilicone oil is dimethyl hydroxysilicone oil with a viscosity-average molecular weight of 1000-5000 and a hydroxyl content of 8.0-9.5%. Silica was sieved through a 1000-mesh sieve; 5000 PPM platinum complex (platinum(0)-divinyltetramethyldisiloxane complex); The inhibitor is 1-ethynyl-1-cyclohexanol.
[0030] Example of preparation of antistatic compound Preparation Example 1 An antistatic compound is prepared by the following method: Weigh out the antistatic agent and silane-containing activator by weight percentage and put them into a planetary mixer and stir for 30 minutes to fully activate the materials and obtain the antistatic filler. Weigh out the silica according to the weight percentage and add it to the antistatic filler. Continue stirring for 30 minutes to ensure that it is fully mixed and homogeneous, and obtain mixture A. Weigh out the raw methyl vinyl silicone rubber and hydroxyl silicone oil and put them into a kneader. Stir at a speed of 60 r / min and heat at 3℃ / min. After stirring for 10 min, add mixture A in 3 portions, stirring for 10 min each time. When the temperature reaches 150℃, keep it at a constant temperature for 2 h, cool to 30℃, and discharge to obtain antistatic compound.
[0031] The particle size of both acetylene black and single-walled carbon nanotubes is 0.001-10 micrometers, and both were sieved through a 2000-mesh sieve in the preparation examples. The siloxane-containing activator is composed of an organosilicon oligomer (methacryloyloxypropyl organosilicon resin) and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine in a weight ratio of 1:1. The specific amounts of the above raw materials are shown in Table 1.
[0032] Preparation Examples 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used is different, as shown in Table 1. Table 1. Raw material usage (wt%) for Preparation Examples 1-3 Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the organosilicon oligomer is a glycidyl etheroxypropyl organosilicon oligomer.
[0033] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that the organosilicon oligomer oil methacryloyloxypropyl organosilicon resin and glycidyl etheroxypropyl organosilicon oligomer are composed in a weight ratio of 1:3.
[0034] Preparation of comparative examples Preparation of Comparative Example 1 The difference between Comparative Example 1 and Preparation Example 1 is that the silane activator is silane coupling agent KH530.
[0035] Preparation of Comparative Example 2 The difference between Comparative Example 2 and Preparation Example 1 is that the silane activator is N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine.
[0036] Preparation of Comparative Example 3 The difference between Comparative Example 3 and Preparation Example 1 is that the silane activator is methacryloyloxypropyl silicone resin.
[0037] Preparation of Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the antistatic agent is acetylene black.
[0038] Preparation of Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the antistatic agent is a single-walled carbon nanotube.
[0039] Preparation of Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the antistatic agent is graphene. Example
[0040] Example 1 An antistatic foamed silicone cushioning component for new energy batteries is prepared by the following method: Based on the weight percentage of the antistatic compound, the antistatic compound obtained in Preparation Example 1 was mixed evenly with 5 wt% sodium bicarbonate and 5 wt% OBSH (4,4'-oxobisbenzenesulfonyl hydrazine) in a two-roll mill. Then, 3.8% hydrogen-containing silicone oil (hydrogen content 1.6%) was added and the mixture was further mixed evenly. Next, 1 wt% inhibitor was added and the mixture was mixed evenly. Finally, 3 wt% platinum vulcanizing agent (5000 PPM platinum complex) was added and the mixture was mixed evenly. Each time an auxiliary agent (sodium bicarbonate and OBSH, hydrogen-containing silicone oil, inhibitor, platinum vulcanizing agent) was added during the above mixing process, the mixture was mixed evenly. The rubber compound is mixed in 30 triangular bundles to ensure thorough and uniform mixing. The mixing temperature must be controlled below 30°C. Otherwise, premature cross-linking and vulcanization of the silicone will occur. The resulting compound is then pressed into 1.5mm sheets using a five-roll calender (the sheets require a 0.1mm thick matte PET backing). The sheets, along with the PET backing, are fed into a tunnel oven for heating, vulcanization, and foaming at 180°C for 30 minutes. After vulcanization, a honeycomb-shaped antistatic foamed silicone cushioning part is obtained.
[0041] Examples 2-8 The difference between Examples 2-8 and Example 1 lies in the source of the antistatic compound, as shown in Table 1. Example Sources of antistatic compound Example 1 Preparation Example 1 Example 2 Preparation Example 2 Example 3 Preparation Example 3 Example 4 Preparation Example 4 Example 5 Preparation Example 5 Example 6 Preparation of Comparative Example 1 Example 7 Preparation of Comparative Example 2 Example 8 Preparation of Comparative Example 3 Comparative Example Comparative Examples 1-3 The difference between Comparative Examples 1-3 and Comparative Example 1 is that the antistatic compound comes from different sources, as shown in Table 2. Table 2 Experimental data for comparative examples 1-3 Comparative Example Sources of antistatic compound Comparative Example 1 Preparation of Comparative Example 4 Comparative Example 2 Preparation of Comparative Example 5 Comparative Example 3 Preparation of Comparative Example 6 Performance testing Detection methods / test methods 1) Hardness: Refer to GB / T 531.1-2008 and use a Shore hardness tester for testing. After overlapping two antistatic foamed silicone cushioning parts, press down the Shore hardness tester and then read the test value.
[0042] 2) Static electricity value (volume resistivity): Tested according to GB / T1410-2006. When the volume resistivity is above 10... 6 -10 8 Ω indicates that the code is qualified.
[0043] 3) Compression set: Tested according to ASTM D395-2003. When the compression set is between 17-21%, it is considered acceptable.
[0044] 4) High and low temperature cycling test: The test sample is placed in a test chamber at 85℃ and 85% humidity for 8 hours, and then placed in an environment at -40℃ and 40% humidity for 8 hours to complete one cycle of thermal shock. This thermal shock cycle is repeated 24 times. Finally, the sample is removed and placed in a drying oven at 60℃ for 2 hours, and then left at room temperature for 24 hours before testing the compression set and electrostatic value. When the electrostatic value is 10... 6 -10 8 Ω is marked as qualified, and the corresponding compression set retention rate is calculated.
[0045] 5) Fatigue resistance test A. Vibration fatigue performance (mechanical property retention after long-term vibration): Referring to ASTM D3518, apply cyclic vibration simulating the actual amplitude to the buffer component, with an amplitude of 1 mm and a frequency of 30 Hz, and accumulate vibration for 100 transport cycles; then place it at room temperature for 24 hours, and then test the compression set and electrostatic value. When the electrostatic value is 106-108 Ω, it is considered qualified, and the corresponding compression set retention rate is calculated.
[0046] B. Impact fatigue performance (mechanical property retention after multiple impacts): Refer to ISO 6603-2 (drop hammer impact), simulate vehicle collision impact with an acceleration of 80G; after 10 impact tests, test the compression set and electrostatic value. When the electrostatic value is 106-108Ω, it is considered qualified, and calculate the corresponding compression set retention rate.
[0047] The compression resilience retention rates are as follows: Grade A ≥ 98%; Grade B < 98%; Grade C < 95%; Grade D < 92%; Grade E < 90%.
[0048] In summary, if all test results in steps 1)-3) are qualified, the overall performance is considered qualified; otherwise, the overall performance is considered unqualified. For each experimental step in steps 1)-5) above, 5 samples are used, and the final experimental results are the average value.
[0049] The specific experimental data are shown in Table 3. Table 3. Experimental data of Examples 1-8 and Comparative Examples 1-3 Based on Example 1 and Comparative Examples 1-3, and referring to Table 3, it can be seen that the overall performance, vibration fatigue performance, and impact fatigue performance of Comparative Examples 1-3 are all unqualified. Furthermore, the compression resilience retention rate of Comparative Examples 1-3 is all at grade D (90% ≤ D grade < 92%) or grade E (E grade < 90%), while that of Example 1 is at grade B, and even reaches grade A (A grade ≥ 98%; 95% ≤ B grade < 98%). This indicates that the present application, through the compounding of acetylene black and single-walled carbon nanotubes, combined with the siloxane-containing activator of the present application, which is composed of organosilicon oligomers and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, can achieve better overall performance and maintain better antistatic and buffering performance under long-term harsh conditions.
[0050] Comparing Examples 1-8, it can be seen that Example 5 achieved Grade A in compression resilience retention rate after high and low temperature cycling tests, vibration fatigue performance tests, and impact fatigue performance tests. This indicates that the composition consists of acetylene black and single-walled carbon nanotubes, and the siloxane activator is composed of organosilicon oligomer (methacryloyloxypropyl organosilicon resin) and organosilicon oligomer oil methacryloyloxypropyl organosilicon resin and glycidyl etheroxypropyl organosilicon oligomer N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine.
[0051] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. An antistatic foamed silicone cushioning component for new energy batteries, characterized in that, This antistatic foamed silicone cushioning component is made by mixing and foaming antistatic compound, foaming agent, hydrogen-containing silicone oil, inhibitor, and platinum catalyst; the antistatic compound is composed of the following raw materials by weight percentage: Methyl vinyl silicone rubber raw rubber 37-50% 38-45% silica Antistatic filler 8-15% Hydroxysilicone oil 1-3%; The antistatic filler is composed of an antistatic agent and a silane-containing activator; the antistatic agent is composed of acetylene black and single-walled carbon nanotubes.
2. The antistatic foamed silicone cushioning component for new energy batteries according to claim 1, characterized in that: The amount of acetylene black used is 4-7 wt%; the amount of single-walled carbon nanotubes used is 2-5 wt%; and the amount of silane-containing activator used is 3-5 wt%.
3. The antistatic foamed silicone cushioning component for new energy batteries according to claim 1, characterized in that: The particle size of both the acetylene black and the single-walled carbon nanotubes is 0.001-10 micrometers.
4. The antistatic foamed silicone cushioning component for new energy batteries according to claim 1, characterized in that: The siloxane-containing activator is composed of organosilicon oligomers and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine.
5. The antistatic foamed silicone cushioning component for new energy batteries according to claim 1, characterized in that: The organosilicon oligomer is a methacryloyloxypropyl organosilicon resin and / or a glycidyl etheroxypropyl organosilicon oligomer.
6. The antistatic foamed silicone cushioning component for new energy batteries according to claim 1, characterized in that: The silica is composed of fumed silica and precipitated silica.
7. The antistatic foamed silicone cushioning component for new energy batteries according to claim 6, characterized in that: The amount of fumed silica is 18-20 wt%, and the amount of precipitated silica is 20-25 wt%.
8. An antistatic foamed silicone cushioning component for new energy batteries according to any one of claims 1-7, characterized in that, The antistatic compound is prepared by the following method: According to the weight percentage, weigh the antistatic agent and the silane-containing activator, mix them evenly, and activate them to obtain the antistatic filler; According to the weight percentage, weigh out methyl vinyl silicone rubber raw rubber, fumed silica, antistatic filler, and hydroxyl silicone oil, and knead them together to obtain an antistatic compound.
9. The antistatic foamed silicone cushioning component for new energy batteries according to claim 1, characterized in that: The foaming agent is composed of sodium bicarbonate and OBSH; the platinum catalyst is a 5000 PPM platinum complex.
10. A method for preparing an antistatic foamed silicone buffer for new energy batteries according to any one of claims 1-9, characterized in that, It is prepared by the following method: Weigh out the antistatic compound and foaming agent by weight percentage, mix them evenly, then add hydrogen-containing silicone oil and continue mixing evenly, then add inhibitor and mix evenly, and finally add platinum vulcanizing agent and mix evenly. The above mixing process is carried out by making triangular bags and keeping the mixing temperature below 30°C. The resulting compound is then pressed into sheets, and the resulting sheets are then foamed to obtain antistatic foamed silicone cushioning parts.
Citation Information
Cited By
Multifunctional group modified hydrogen-containing polysiloxane, preparation method and application in flame-retardant antistatic silicone rubber coating
CN121628117A
Addition type silicone rubber with flame-retardant and antistatic functions as well as preparation method and application of addition type silicone rubber
CN121628389A